Fourier Transform Infrared Sebagai Metode Alternatif Penetapan Tingkat Stres pada Sapi (FOURIER TRANSFORM INFRARED AS AN ALTERNATIVE TOOL FOR DETERMINING OF STRESS IN COW) - Astuti, Pudji; Airin, Claude Mona; Widiyanto, Slamet; Hana, Amelia; Maheshwari, Hera; Sjahfirdi, Luthfiralda (Jurnal Veteriner; Vol 15 No 1 (2014), 2014)
Stress in animal is a condition of nonspesific discomfort which cause of non-specific immune defects,failure of reproduction, and decreased of meat carcass until the death of  animals. To determine stress ofcattle,  it will be invented stress detector using a non-invasive method based on the spectroscopy FourierTransform Infrared (FTIR). Basically,  FTIR will detect component in compound of cathecolamine andcortisol as ketone (= O) and methyl (= CH 3). Furthermore, each group of components will be detected indifferent of absorbant and wavelength.   The results showed that average level of cortisol in female beefcattle durimg resting eriod was 38,48±21,53 ng/dL, on time of slaughtering were 116,88±112,59 ng/dL. Forbull, which were resting  20,42±9,25 ng/dL; when animal was slaughtered level of cortisol was  67,61±41,62ng/dL. Using FTIR, it was showed that compound of metil was absorbed well. Animals with udder stresscondition have been recorded on the wave lenght of 2777-3456 nm.   It has been concluded level of cortisolon cattle which were resting is significantly different from animal which were slaughtering P(< 0.05),where cortisol would increase drastically. Using Calibration of FTIR indicated resting animals only havefewer value of absorbance than animals which slaughtered.  FTIR is a very prospect method for makingstress indicator.
Keywords: cortisol, FTIR, stress, resting period, ELISA